El inicio de la Segunda Guerra Mundial visto desde la prensa Ecuatoriana. - Trujillo Flores, Edwin Joel (2025)
This research, entitled "The Beginning of World War II as Seen from the Ecuadorian Press," analyzes how two Ecuadorian newspapers covered the outbreak of the conflict between September 1 and 27, 1939. Through a comparative approach, the study identifies predominant themes and describes key events as presented by the press. The findings reveal that both newspapers reported on the conflict using distinctly different tones. El Día employed alarmist and critical language, particularly toward Germany, while El Telégrafo adopted a more neutral, descriptive narrative centered on the progression of events. Despite their tonal differences, both newspapers highlighted the devastation caused by the war and the Polish resistance efforts. A comparison with Martin Gilbert’s book The Second World War confirms that the newspapers reported several factual details, including the bombings and the fall of Warsaw. However, the coverage notably omits critical aspects, such as the extent of German repression following Poland’s surrender. This study underscores the essential role of the media in shaping public perception during international crises. It also suggests that extending this type of analysis to other Latin American countries could provide deeper insights into media influence and narrative construction during times of war.